Psychological Capital and Academic Procrastination: The Mediating Role of Self-Regulated Learning among College Students - Tira Nalvianti Rahmi; Shahnaz Safitri (Universitas Ahmad Dahlan, 2023)
Academic procrastination has always posed a challenge in both offline and online learning environments. In order to mitigate delays in academic assignments, students need to adopt positive attitudes towards their academic life and actively regulate their learning process. Therefore, this study aimed to investigate the mediating role of self-regulated learning in the relationship between psychological capital and academic procrastination among college students. The study utilized the Academic Psychological Capital Questionnaire-12, the Motivated Strategies for Learning Questionnaire, and the Academic Procrastination Scale. The findings, based on a sample of 207 college students from Indonesia, revealed that self-regulated learning fully mediated the link between psychological capital and academic procrastination. Moreover, further analysis indicated that the method of learning could differentiate levels of academic procrastination, while no significant difference was observed based on gender. This study offers valuable insights to students, lecturers, and other stakeholders in the field of education, emphasizing the significance of psychological capital and self-regulated learning in students' academic journey.